Improvement in Curcumin’s Stability and Release by Formulation in Flexible Nano-Liposomes - Hua-Wei Chen; Su-Der Chen; Hung-Ta Wu; Chun-Hung Cheng; Chyow-San Chiou; Wei-Ting Chen (Nanomaterials)
Curcumin is utilized extensively as Chinese medicine in Asia due to its antioxidant, antimicrobial, and inflammatory activities. However, its use has the challenges of low oral bioavailability and high heat sensitivity. The aim of this research was to produce flexible nano-liposomes containing curcumin using an innovative approach of ethanol injection and Tween 80 to enhance the stability and preservation of curcumin. The mean particle size, encapsulation efficiency, thermal degradation, storage stability, and curcumin release in flexible nano-liposomes were also investigated. We found that the mean particle size of curcumin-loaded flexible nano-liposome decreased from 278 nm to 27.6 nm. At the same time, the Tween 80 concentration increased from 0 to 0.15 wt%, which corresponded with the results of transmission electron microscopy (TEM) morphology analyses, and particle size decreased with an enhancement in Tween 80 concentration. Further, pure curcumin was quickly released within one hour at 37 °C, and first-order kinetics matched with its release curve. However, curcumin encapsulated in flexible nano-liposomes showed a slow release of 71.24% within 12 h, and a slower release pattern matched with the Higuchi model over 24 h, ultimately reaching 84.63% release. Hence, flexible nano-liposomes of curcumin made by a combination of ethanol injection and Tween 80 addition prevented the thermal degradation of curcumin, and enhanced its storage stability and preservation for future drug delivery applications.